Effects of slow-and controlled-release nitrogen fertilizer on nitrogen utilization characteristics and yield of machine-transplanted rice - Li Yue; Li Yinghong; Zhao Jianhong; Sun Yongjian; Xu Hui; Yan Fengjun; Xie Huaying; Ma Jun (浙江大学学报. 农业与生命科学版)
In order to reduce artificial inputs and improve the efficiency of crop production, the slow- and controlled-release nitrogen (N) fertilizer has become a research focus. However, relatively little work has been done on slow- and controlled-release N fertilizer in machine-transplanted rice. Few studies were reported on whether slow- and controlled-release N fertilizer can improve machine-transplanted rice yield and simplify the fertilization technique. Therefore, different slow-and controlled-release N fertilizers and varieties under machine-transplanted rice were set in this paper, to explore effects of slow- and controlled-release N fertilizer on N utilization characteristics and yield in machine-transplanted rice.Two-factor split-plot design was used to explore the slow-and controlled-release N fertilizer to improve N utilization efficiency and yield increasing mechanism in machine-transplanted rice. Early-maturing indica rice Zhongjiazao 17 and medium-late indica hybrid rice Chuanguyou 7329 were used as trial varieties. The main plot treatments were variety types. The subplot treatments were the coated slow-and controlled-release N fertilizer with nitrification inhibitor applied before transplanting (N1), sulfur-coated slow-and controlled-release N fertilizer applied before transplanting (N2), two resin-coated slow- and controlled-release N fertilizer applied before transplanting (N3, N4), single basal application of urea (N5), and the urea application proportion of base, tillering and spike fertilizers was 5∶3∶2 (N6).The results showed significant interactions between variety types and slow-and controlled-release N fertilizers application on biomass, N accumulation, translocation and grain yield at main growth stages. The N apparent use-efficiency was much improved when resin-coated slow-and controlled-release N fertilizer was applied. Besides, N accumulation of panicle, partial factor productivity of applied N, N agronomic efficiency, N apparent use efficiency and yield were increased by 51.83%, 18.71%, 57.97% and 5.54% compared to N6, respectively. Resin-coated slow-and controlled-release N fertilizer was the best among the slow-and controlled-release N fertilizers tested in machine-transplanted rice, which had a significant effect on N accumulation and use efficiency in medium-late indica hybrid rice. However, sulfur-coated slow- and controlled-release N fertilizer and coated slow- and controlled-release N fertilizer with nitrification inhibitor were lower than conventional fertilization in increasing yield and synergism, but they were effective for translocation of vegetative organs and N transportation efficiency. In addition, long growth period of late maturity hybrid rice Chuanguyou 7329 formed sufficient panicles and structure optimization of high quality group, and the rice could fully carry out construction of source-sink and accumulation of dry matter at full heading stage. And from full heading stage to mature stage, dry matter accumulation was improved steadily, and nitrogen accumulation increased N translocation of vegetative organs during grain filling. Ultimately, the late hybrid rice was significantly higher than early-maturing rice in N accumulation, translocation and yield at different growth stages. However, the efficiency of N utilization in Chuanguyou 7329 was low because of its low efficiency of the stem and leaf translocation.In conclusion, under the experimental condition, resin-coated N fertilizer in combination with medium-late indica hybrid rice is the optimal treatment for high yield and high N use efficiency.